Exploiting Antitumor Immunotherapeutic Novel Strategies by Deciphering the Cross Talk between Invariant NKT Cells and Dendritic Cells - Fujii, Shin-ichiro; Shimizu, Kanako (Frontiers in Immunology, 2017)
Immune checkpoint blockade therapy has prevailed for several types of cancer; however, its effectiveness as a single therapy is still limited. In principle, dendritic cells (DCs) should be able to control the post-therapy immune response, in particular since they can link the two major arms of the immune system: innate and adaptive immunity. Therefore, DCs would be a logical and ideal target for the development of immunotherapies. Since DCs are not activated in the steady state, an adjuvant to convert their function from tolerogenic to immunogenic would be desirable. Upon ligand activation, invariant natural killer T (iNKT) cells simultaneously activate NK cells and also energize the DCs, resulting in their full maturation. To utilize such iNKT-licensed “fully” matured DCs as adjuvants, mechanisms of both intercellular communication between DC subsets and iNKT cells and intracellular molecular signaling in DCs have to be clarified and optimized. To generate both innate and adaptive immunity against cancer, a variety of strategies with the potential to target iNKT-licensed DCs in situ have been studied. The benchmark of success in these studies, each with distinct approaches, will be the development of functional NK cells and cytotoxic T cells (CTLs) as well as generation of long-term, memory CTL. In this review, we provide a framework for NKT-mediated immunotherapy through selective DC targeting in situ, describe progress in the design of licensed therapies for iNKT cell targeting of DCs, and highlight the challenge to provide maximal benefit to patients.